Development of a Wearable Wide band Antenna in the Frequency Range of 2.4 GHz and 5.2 GHz - Soares, Fidelio; Eko Tjipto Rahardjo (Universitas Indonesia, 2024)
This paper presents the optimization and design of a wearable multiband microstrip patch antenna using jeans as a substrate material for wireless communication applications. The proposed antenna operates at 2.4 GHz, 5.2 GHz, and 5.6 GHz frequency bands, which are essential for Wi-Fi and other wireless standards. The antenna design incorporates a rectangular slot and patch to achieve triple-band operation with a full ground plane, ensuring good isolation, directional radiation patterns, and high gain. Simulations and measurements were conducted using CST STUDIO SUITE software and standard laboratory equipment to validate the antenna's performance. Results demonstrate return losses greater than -10 dB with bandwidths of 72.5 MHz, 169.1 MHz, and 127.7 MHz for each band, respectively. The antenna achieves gain values of 0.886 dBi, 6.38 dBi, and 5.27 dBi for the 2.4 GHz, 5.2 GHz, and 5.6 GHz bands. Flexibility tests confirm the antenna's suitability for wearable applications, maintaining performance despite bending. The proposed antenna shows significant potential for integration into wearable devices, providing a reliable and efficient solution for modern wireless communication needs.